Case Study of Pediatric Cerebral Sinus Venous Thrombosis Center of a Low Middle-Income Country. (16th June 2021) - Moiz, Bushra; Ukrani, Ronika Devi; Arif, Aiman; Akbar, Inaara; Sadiq, Muhammed Wahhaab; Altaf, Sadaf
Pediatric cerebral venous sinus thrombosis (CVST) is rare but a potentially fatal disease requiring its understanding in local setting. In this study, we observed the clinical course, management, and outcome of pediatric patients with sinus thrombosis in a tertiary care center at Pakistan. Patients between age 0 to 18 years of both genders diagnosed with sinus thrombosis during 2011 to 2020 were included. Data was collected through in-house computerized system and SPSS version 19 was used for analysis. Of 143492 pediatric admissions, 32 (21 males and 11 females) patients with a median (IQR) age of 4.5 years (0-16) had CVST. This is equivalent to 18.5 CVST events per million pediatric admissions. Adolescents were mostly affected, and the overall mortality was 7%. Primary underlying disorders were infections (59%), hematological neoplasms (12.5%), thrombotic thrombocytopenic purpura (3%) and antiphospholipid syndrome (3%). Activated protein C resistance (44%) was the most common inherited thrombophilia. Twenty-one (66%) patients were anemic with a mean (±SD) hemoglobin of 9.0 g/dL (±2.3). Regression analysis showed a positive association of anemia with multiple sinus involvement ( P -value 0.009) but not with duration of symptoms ( P -value 0.344), hospital stay ( P -value 0.466), age ( P -value 0.863) or gender ( P -value 0.542) of the patients. SARS-COV2 was negative in patients during 2020. Adolescents were primarily affected by sinus thrombosis and infections was the predominant risk factor for all age groups, with a low all-cause mortality. A high index of clinical suspicion is required for prompt diagnosis and intervention.